A Conceptual Study on The Impact of Hybrid Work Models on Work-Life Balance and Employee Well-Being in The IT Sector of Tamil Nadu - Gurusamy , Dr. P.; Visithra , A. (International Journal of Accounting and Economics Studies, 2025)
The COVID-19 pandemic has been a game-changer in work practices globally, and there is a rapid shift to hybrid working systems, which combine working at home and in-office work. It is an analytical paper, i.e., conceptual in nature. It is studying the Impact of hybrid work patterns on work-life balance & employee well-being in the IT industry of Tamil Nadu, India. Based on the existing theory available on Self-Determination Theory, Boundary Theory, and work-life interface Model, the current study suggests a conceptual framework in which hybrid working models mediate work-life balance through the fundamental mediating variables, which include autonomy, flexible working time, technology readiness, and home environment. No primary data is collected in this study, but it is based on which future empirical studies and policy making can be conducted. It has practical implications for HR managers, policymakers, and IT firms who will aim to designate effective hybrid work policies that are situated in regional realities. Finally, the article will help to increase the overall knowledge base related to the future-of-work strategies in emerging economies.